2006
DOI: 10.1083/jcb.200509115
|View full text |Cite|
|
Sign up to set email alerts
|

Functional modulation of IFT kinesins extends the sensory repertoire of ciliated neurons in Caenorhabditis elegans

Abstract: The diversity of sensory cilia on Caenorhabditis elegans neurons allows the animal to detect a variety of sensory stimuli. Sensory cilia are assembled by intraflagellar transport (IFT) kinesins, which transport ciliary precursors, bound to IFT particles, along the ciliary axoneme for incorporation into ciliary structures. Using fluorescence microscopy of living animals and serial section electron microscopy of high pressure–frozen, freeze-substituted IFT motor mutants, we found that two IFT kinesins, homodimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
170
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(180 citation statements)
references
References 31 publications
9
170
1
Order By: Relevance
“…A limited role for kif17 in zebrafish ciliogenesis, especially in double mutants with kif3b, is surprising, given the prominent function of this kinesin in C. elegans cilia (31,36). In vertebrates, the function of kif17 has been studied in tissue culture as well as in mouse and zebrafish models.…”
Section: Discussionmentioning
confidence: 99%
“…A limited role for kif17 in zebrafish ciliogenesis, especially in double mutants with kif3b, is surprising, given the prominent function of this kinesin in C. elegans cilia (31,36). In vertebrates, the function of kif17 has been studied in tissue culture as well as in mouse and zebrafish models.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used a model organism, C. elegans. In C. elegans, 60 of the 302 neurons of the hermaphrodite are ciliated sensory neurons, and several works have demonstrated that the mutants of IFT-related genes show defects in sensory functions (Cole et al 1998;Signor et al 1999;Qin et al 2001;Haycraft et al 2003;Schafer et al 2003;Blacque et al 2004;Scholey et al 2004;Snow et al 2004;Ou et al 2005;Bell et al 2006;Evans et al 2006). In the present work, we identified nematode IFT-81 and IFT-74, whose C. reinhardtii orthologues were recently shown to form core complex in subcomplex B (Lucker et al 2005), and attempted to elucidate their physiological roles in C. elegans.…”
Section: Introductionmentioning
confidence: 94%
“…This homodimeric kinesin-2 motor was first characterized in C. elegans where it is known as OSM-3 (Shakir et al, 1993;Signor et al, 1999b), and it has subsequently been identified in cilia of Tetrahymena and some vertebrate cell types, where it is named Kin5 and KIF17, respectively (Awan et al, 2004;Setou et al, 2000). Genetic and motility studies in C. elegans have suggested that OSM-3 functions as an accessory anterograde IFT motor involved in the assembly or function of specific subsets of sensory cilia, thereby contributing to the generation of ciliary structural and functional diversity (Evans et al, 2006;Mukhopadhyay et al, 2007). For example, in the C. elegans amphid channel cilia, OSM-3 appears to cooperate with kinesin-II to drive anterograde IFT along the middle segment of the cilia, where the axoneme consists of doublet MTs; OSM-3 alone mediates anterograde transport along the distal segment, which contains singlet MTs (Snow et al, 2004).…”
Section: Anterograde Ift Motorsmentioning
confidence: 99%